1998
DOI: 10.1016/s0022-5347(01)63936-3
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional Sclerotherapy in the Management of Hemangiomas of the Glans Penis

Abstract: Intralesional sclerotherapy is a cost-effective modality for the treatment of glans penis hemangiomas, especially in developing countries and at peripheral hospitals where expensive laser equipment may not be available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…Hemel and colleagues treated four cases of penile hemangiomas with sclerotherapy (30% hypertonic solution) and concluded that the technique is safe, manageable, and inexpensive 25 …”
Section: Discussionmentioning
confidence: 99%
“…Hemel and colleagues treated four cases of penile hemangiomas with sclerotherapy (30% hypertonic solution) and concluded that the technique is safe, manageable, and inexpensive 25 …”
Section: Discussionmentioning
confidence: 99%
“…Because it can be applied within a few seconds under local anesthesia with favorable cosmetic results, it should be considered in small hemangiomas or adjuvant to the other treatment modalities [8]. Successful sclerotherapy with intralesional injection of 30% hypertonic saline has been reported by Hemal et al in 4 patients with penile hemangioma [11]. They conclude that intralesional sclerotherapy is a cost-effective modality in case of the unavailability of other techniques such as electrofulguration or laser coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it should be considered for voluminous hemangiomas as well. The risk of large volume of skin loss or development of the undesirable scar tissue formation replaced the surgical option with fulguration of the lesion, cryosurgery, laser ablation, or sclerotherapy [9,[11][12][13]. Laser therapy is a safe method in the treatment of vascular lesions of children [14].…”
Section: Discussionmentioning
confidence: 99%
“…Nd:YAG laser treatment has been reported to be effective and safe; however, it is associated with a high risk of scarring and a high incidence of recurrence 10,11 . Sclerotherapy has recently been reported as a good option in the treatment of vascular malformations and has provided excellent aesthetic and functional results even for lesions situated on the glans 4–7 . Direct intralesional injection of a sclerosing agent makes it possible to obliterate blood vessels by local endothelial destruction, with sludging of red blood cells and subsequent thrombosis, eventually leading to intimal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although they are usually small in size and of little clinical importance, they may give rise to psychological discomfort and occasionally require emergency surgery if traumatized 1–3 . Therapeutic options include surgery, electrofulguration, cryotherapy, and recently laser treatment and sclerotherapy 4–7 . Sclerotherapy seems to be effective and economical, with fewer risks than other treatments; although being new, it has been used in a relatively small number of cases and never in dermatology 4–7 .…”
mentioning
confidence: 99%